Inter-limb differences in upper quarter mobility/stability are not associated with performance in competitive swimmers - Borgmann, Katharina; Panzer, Stefan; Limpach, Sam; Muehlbauer, Thomas (Frontiers in Sports and Active Living, 2024)
Background The Y Balance Test–Upper Quarter (YBT–UQ) is a cost-effective, well-established, closed kinetic chain test to assess inter-limb asymmetries in the upper quarter that could negatively affect swimming performance. Thus, the aim of the present study was to determine YBT–UQ performances and inter-limb differences as well as its association with swimming performance in athletes with diverging levels of expertise. Methods Forty female and male competitive swimmers (age range: 10–22 years) with different expertise levels (A-squad: n = 9, B-squad: n = 12, C-squad: n = 19) were tested (reach distances for the YBT–UQ) and swimming performance was calculated using the ratio of individual to world best time. Results YBT–UQ performances (i.e., inferolateral reach direction for the dominant arm: p = .027, ηp2 = .12 and the non-dominant arm: p = .031, ηp2 = .17) but not YBT–UQ inter-limb differences significantly differed between groups and were largest in swimmers with the lowest expertise level (i.e., C-squad). Further, YBT–UQ performances (i.e., inferolateral reach direction [r = −.68 to −.70, both p < .05] and composite score [r = −.65 to −.67, both p < .05] for both arms and medial reach direction for the non-dominant arm [r = −.64, p < .05]) but not inter-limb differences were significantly and negatively correlated with swimming performance among B-squad swimmers. Conclusions Our results suggest that inter-limb differences in upper quarter mobility/stability are not influenced by the level of expertise and have no significant associations with swimming performance. However, greater reach distances were correlated with lower swimming performance for the B-squad swimmers indicating that a training-related increase in upper quarter mobility/stability could worsen swimming performance in those athletes.